Studi Peran Citra Perusahaan Dalam Meningkatkan Motivasi Kerja Karyawan PT. PAL Indonesia (Persero) - Ulfatus Solikha,; Muhammad Isa Anshori, (Manajemen Kreatif Jurnal, 2024)
This study investigates the factors that influence the formation of PT's corporate image. Pal Indonesia (Persero) and how this perception is related to employee work motivation. Through a literature analysis approach, this research analyzes the perceptions of various stakeholder groups, including prospective employees, customers, suppliers and the general public. The results of the analysis show that company reputation, product and service quality, relationships with stakeholders, organizational values, and commitment to social responsibility are the main factors that influence the company's image. Positive perceptions of the company's image can increase trust, reputation and support from various parties, which in turn can motivate employees to provide their best contribution. Conversely, negative or ambiguous perceptions can reduce employee interest and motivation. Therefore, company management must actively monitor and manage these factors, and strive to build good relationships with various stakeholders to create a motivating work environment that contributes to the company's long-term success.